Motion integration for optic-flow patterns : the interaction between local and global noise - Chu, Ann Ning (2016)
In the visual system, both the local and global stages of motion processing are susceptible to noise. Given the hierarchical nature of motion processing, do local and global noise interact with each other? If such interaction exists, does it differ across different types of optic-flow patterns? These questions were addressed using a novel psychophysical technique, in which uncertainty at the local and global stages of motion processing was independently manipulated within the same motion stimulus. We used a multiple-aperture stimulus, which consisted of an array of randomly-oriented, drifting Gabor elements (Amano, Edwards, Badcock, & Nishida, 2009). Global noise was manipulated based on motion coherence and global signal-to-noise ratio (global-SNR) was defined as the ratio between signal and noise element numbers. Local noise, defined as the ratio between the contrasts of Gabor patches and contrast of noise pixels, was introduced by superimposing dynamic-noise pixels on each drifting Gabor patch at every motion frame. Observers performed a two-choice, global-direction-discrimination task on three optic-flow patterns: translational (left or right), circular (clockwise or anticlockwise), and radial (inward or outward). In each block of trials, the local-signal-to-noise-ratio (local-SNR) was fixed and the 75%-accuracy threshold in terms of global-SNR was measured. For all three optic-flow patterns, we found a “trade-off” between local and global noise: global-SNR thresholds decreased log-linearly as local-SNR increased, suggesting an interaction between local and global noise. Beyond a certain local-SNR level, global-SNR thresholds remained constant. This saturation point was lower for circular compared to radial and translational motion, suggesting that global integration mechanisms for circular motion are less susceptible to local noise disturbances.